Membangun Keunggulan Bersaing Perusahaan Melalui Penciptaan Nilai - Fita Andriyani; Jeni Susyanti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze how value creation through business model innovation can build a company's competitive advantage in facing rapid and complex market dynamics. Employing a conceptual approach, the study examines recent literature on value creation strategies, business model innovation, and dynamic organizational capabilities. The analysis reveals that companies capable of reconstructing their value propositions, integrating digital technologies, and developing adaptive capabilities are more likely to create sustainable value and maintain a competitive edge. However, challenges such as imitation risks and organizational culture shifts must be addressed through holistic and sustainable innovation strategies.